Utility of HR-pQCT in detecting training-induced changes in healthy adult bone morphology and microstructure - Sekel, Nicole M.; Hughes, Julie M.; Sterczala, Adam J.; Mroz, Kelly H.; Lovalekar, Mita; Cauley, Jane; Greeves, Julie P.; Nindl, Bradley C. (Frontiers in Physiology, 2023)
Healthy bone adjusts its traits in an exceptionally coordinated, compensatory process. Recent advancements in skeletal imaging via High-Resolution Peripheral Quantitative Computed Tomography (HR-pQCT) allows for the in vivo 3-dimensional and longitudinal quantification of bone density, microarchitecture, geometry, and parameters of mechanical strength in response to varying strain stimuli including those resulting from exercise or military training. Further, the voxel size of 61 microns has the potential to capture subtle changes in human bone in as little as 8 weeks. Given the typical time course of bone remodeling, short-term detection of skeletal changes in bone microstructure and morphology is indicative of adaptive bone formation, the deposition of new bone formation, uncoupled from prior resorption, that can occur at mechanistically advantageous regions. This review aims to synthesize existing training-induced HR-pQCT data in three distinct populations of healthy adults excluding disease states, pharmacological intervention and nutritional supplementation. Those included are: 1) military basic or officer training 2) general population and 3) non-osteoporotic aging. This review aims to further identify similarities and contrasts with prior modalities and cumulatively interpret results within the scope of bone functional adaptation.